Ageing stereotypes and prodromal Alzheimer’s disease (AGING): study protocol for an ongoing randomised clinical study - Ahmed Abbas; Didier Hannequin; Olivier Martinaud; David Wallon; Vincent de la Sayette; Adrien Julian; Marc Paccalin; Julien Cogez; Kim Gauthier; Alexandrine Morand; Frederic Dutheil; Béatrice Alescio-Lautier; et al. (BMJ Open)
Introduction The number of older people diagnosed with amnestic mild cognitive impairment (aMCI), the prodromal state of Alzheimer's disease (AD), is increasing worldwide. However, some patients with aMCI never convert to the AD type of dementia, with some remaining stable and others reverting to normal. This overdiagnosis bias has been largely overlooked and gone unexplained. There is ample evidence in the laboratory that negative ageing stereotypes (eg, the culturally shared belief that ageing inescapably causes severe cognitive decline) contribute to the deteriorating cognitive performances of healthy older adults, leading them to perform below their true abilities. The study described here is intended to test for the first time whether such stereotypes also impair patients’ cognitive performances during neuropsychological examinations in memory clinics, resulting in overdiagnosis of aMCI.Methods and analysis The ongoing study is a 4-year randomised clinical trial comparing patients’ physiological stress and cognitive performances during neuropsychological testing in memory clinics. A total of 260 patients attending their first cognitive evaluation will be randomised to either a standard condition of test administration, assumed here to implicitly activate negative ageing stereotypes or a reduced-threat instruction condition designed to alleviate the anxiety arising from these stereotypes. Both groups will be tested with the same test battery and stress biomarkers. For 30 patients diagnosed with aMCI in each group (n=60), biomarkers of neurodegeneration and amyloidopathy will be used to distinguish between aMCI with normal versus abnormal AD biomarkers. A 9-month follow-up will be performed on all patients to identify those whose cognitive performances remain stable, deteriorate or improve.Ethics and dissemination This protocol has been approved by the French National Agency for Medicines and Health Products Safety and the Sud-Est I French Ethics Committee (2017-A00946-47). Results will be published in peer-reviewed journals.Trial registration number NCT03138018.